Answer:
5x^7 + 4x^4 - 2x^2 + 5x - 19
Step-by-step explanation:
Start by copying 5x -10 +3x^4 - 2x^2 here. Next, add x^4 to +3x^4, -9 to -10, and 5x^7:
5x - 10 +3x^4 - 2x^2
- 9 +x^4 + 5x^7
-----------------------------------------
5x - 19 + 4x^4 - 2x^2 + 5x^7
Now rearrange these terms in descending order by powers of x:
5x^7 + 4x^4 - 2x^2 + 5x - 19 (answer)
Answer:
Dude the answer is 8!
Step-by-step explanation:
You literally multiply the two together. Come on man...
Step 1: Simplify both sides of the equation.
−36=p−30
Step 2: Flip the equation.
p−30=−36
Step 3: Add 30 to both sides.
p−30+30=−36+30
p=−6
Answer:
68in
Step-by-step explanation:
l = 3w-16
l-3w = -16
l+w = 96
-4w = -112
w = 28 in
l = 96-28 = 68in
Answer:
x^7 + x^6 - 3x^4 + 4x^3 + 6x - 3.
Step-by-step explanation:
(x3 + 2x - 1) (x4 - x3 + 3)
= x^7 - x^6 + 3x^3 + 2x^6 - 2x^4 + 6x - x^4 + x^3 - 3
= x^7 + x^6 - 3x^4 + 4x^3 + 6x - 3.